Clinical evaluation of the Tokyo Guidelines 2013 for severity assessment of acute cholangitis. (December 2014) - Nishino, Takayoshi; Hamano, Tetsuya; Mitsunaga, Yutaka; Shirato, Izumi; Shirato, Miho; Tagata, Tomoko; Shimada, Masahiko; Yoshida, Shuhei; Mitsunaga, Atsushi
Abstract Background We evaluated the severity assessment criteria for acute cholangitis (AC) of the Tokyo Guidelines 2013 (TG13) and developed a scoring system for predicting the need for urgent/early biliary drainage. Methods We retrospectively reviewed 66 AC cases prospectively managed based on the TG07 and divided into an urgent/early biliary drainage group (n = 30) and elective biliary drainage group (n = 36). Results There were 26 mild, 27 moderate, and 13 severe cases based on the TG13. The TG13 assessment in 12 of the 17 cases requiring early biliary drainage based on the TG07 was moderate, but underestimated the other five cases as mild AC. When five predictors (blood urea nitrogen >20 mg/dL, SIRS presence, platelet count <120 000/μL, serum albumin level <3.0 g/dL, age ≥75 years old) were used to devise a scoring system, the receiver‐operator characteristic curve of the scores showed good test performance for predicting the need for urgent/early biliary drainage. The area under the curve (AUC) was 0.95 and higher than the TG13 AUC (0.80). Conclusions The TG13 is practical, but some AC cases requiring urgent/early biliary drainage were underestimated as mild AC. The scoring system allows identification of high‐risk AC patients and will improve the TG13.